(untitled) (Journal of Parents and Teachers, 2016)
In the fifty anniversary of the journal, this article consists in the developed pedagogic experience in the journal of Parents and Teachers throughout the articles related to films to bring up values, which it is exposed the path followed for about two decades. This trajectory is innovative and it has been useful in the permanent formation in the different educational stages.